2009
DOI: 10.1021/ja9047762
|View full text |Cite
|
Sign up to set email alerts
|

Pt-Catalyzed Enantioselective Diboration of Terminal Alkenes with B2(pin)2

Abstract: The Pt-catalyzed enantioselective addition of bis(pinacolato)diboron to simple monosubstituted alkenes is described. This reaction occurs in the presence of a readily available chiral phosphonite ligand and is effective with a variety of terminal alkene substrates. Importantly, the reaction can operate with catalyst loadings of only 1 mol% Pt. While oxidation of the intermediate 1,2-bis(boronate) ester provides the chiral 1,2-diol as the reaction product, the intermediate may also be subjected to homologation/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(56 citation statements)
references
References 39 publications
0
53
0
3
Order By: Relevance
“…In contrast to related transformations of monoalkynes, [29] monitoring the reaction progress by multinuclear NMR spectroscopy revealed the gradual disappearance of the starting materials, and the formation of two distinct compounds in benzene solution at elevated temperatures. Both species feature similar resonances in the 1 H, 11 B, and 13 C NMR spectra, which we rationalized by the generation of diastereomeric species. Complexes 4 and 5 were eventually isolated after workup as orange, moderately moisture-sensitive powders.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…In contrast to related transformations of monoalkynes, [29] monitoring the reaction progress by multinuclear NMR spectroscopy revealed the gradual disappearance of the starting materials, and the formation of two distinct compounds in benzene solution at elevated temperatures. Both species feature similar resonances in the 1 H, 11 B, and 13 C NMR spectra, which we rationalized by the generation of diastereomeric species. Complexes 4 and 5 were eventually isolated after workup as orange, moderately moisture-sensitive powders.…”
mentioning
confidence: 59%
“…Along with hydroboration, [1][2][3][4] transition-metalcatalyzed diboration [5] has become useful for the functionalization of unsaturated organic compounds. [6,7] This reaction is widely applicable to substrates such as alkynes [8,9] arynes, [10] alkenes, [11][12][13] carbenoids, [14,15] as well as diazo [16] and carbonyl compounds. [17][18][19][20] Although bis(catecholato)diborane(4) and bis(pinacolato)diborane(4) represent by far the most commonly employed diborane(4) species, the reaction is not restricted to their use.…”
mentioning
confidence: 99%
“…When we subjected model substrate 32 to the conditions described in the study of Morken's group, 42 we observed the syn product with complete selectivity by 13 C-NMR spectroscopy (Fig. 6, ESI †).…”
Section: 40mentioning
confidence: 94%
“…66,67 Diborations have been well developed with transition metal catalysts. [68][69][70] They are useful transformations for the introduction of new functional groups into a molecule.…”
Section: Diborationmentioning
confidence: 99%